KEPUASAN DAN LOYALITAS KONSUMEN RESTORAN McDonald’s DI KOTA DENPASAR - Putu Mira Astuti Pranadewi (JURNAL GASTRONOMI INDONESIA, 2017)
The rapid growth of economic sector in Bali, especially in Badung regency and Denpasar city has stimulated the growth of McDonald’s restaurant on these area. The consumption pattern of local community also changed regarding the growth of financial income. Because of tight competition in fast food service business as a crucial reason, this local market segment should be grapped as much as possible by McDonald’s in Denpasar city. This research was undertaken between Septemberto November 2016. In this case, consumer loyalty is the most important company’s objective. Consumer loyalty could be achieved by providing a good service experience at McDonald’s. As a result there’s a causal relationship between service quality, customer satisfaction, and customer loyalty at restaurant business. Customer loyalty describe the customer willingness to consumedrestaurant’s products or services regularly on a long term period and recommend their friends or relatives to consumed products or services at the same restaurant. Speed of service, access, physical features, assurance, staff attitude, security, and understanding customer are factors that influences customer satisfaction at McDonald’s restaurant.